A frequency‐domain approach for damage detection in welded structures. Issue 4 (21st January 2021) - Ronchei, Camilla; Vantadori, Sabrina; Carpinteri, Andrea; Iturrioz, Ignacio; Rodrigues, Roberto Issopo; Scorza, Daniela; Zanichelli, Andrea
Abstract: The goal of the present paper is to apply a multiaxial fatigue criterion, formulated in frequency‐domain, to welded components. In particular, the proposed procedure requires (i) to evaluate the stress field at the so‐called hotspot and (ii) to compute the fatigue damage. A case study, represented by fillet‐welded tubular T‐joints under random loading, is examined to assess the validity of the above procedure in estimating the crack nucleation position. Finally, the above theoretical results are also compared with those derived by means of a similar procedure, which has recently been proposed by some of the present authors, but formulated in time‐domain.